The interaction networks of small rubber particle proteins in the latex of Taraxacum koksaghyz reveal diverse functions in stress responses and secondary metabolism - Wolters, Silva Melissa; Laibach, Natalie; Riekötter, Jenny; Roelfs, Kai-Uwe; Müller, Boje; Eirich, Jürgen; Twyman, Richard M.; Finkemeier, Iris; Prüfer, Dirk; Schulze Gronover, Christian (Frontiers in Plant Science, 2024)
The Russian dandelion (Taraxacum koksaghyz) is a promising source of natural rubber (NR). The synthesis of NR takes place on the surface of organelles known as rubber particles, which are found in latex – the cytoplasm of specialized cells known as laticifers. As well as the enzymes directly responsible for NR synthesis, the rubber particles also contain small rubber particle proteins (SRPPs), the most abundant of which are SRPP3, 4 and 5. These three proteins support NR synthesis by maintaining rubber particle stability. We used homology-based searches to identify the whole TkSRPP gene family and qPCR to create their spatial expression profiles. Affinity enrichment-mass spectrometry was applied to identify TkSRPP3/4/5 protein interaction partners in T. koksaghyz latex and selected interaction partners were analyzed using qPCR, confocal laser scanning microscopy and heterologous expression in yeast. We identified 17 SRPP-like sequences in the T. koksaghyz genome, including three apparent pseudogenes, 10 paralogs arranged as an inverted repeat in a cluster with TkSRPP3/4/5, and one separate gene (TkSRPP6). Their sequence diversity and different expression profiles indicated distinct functions and the latex interactomes obtained for TkSRPP3/4/5 suggested that TkSRPP4 is a promiscuous hub protein that binds many partners from different compartments, whereas TkSRPP3 and 5 have more focused interactomes. Two interactors shared by TkSRPP3/4/5 (TkSRPP6 and TkUGT80B1) were chosen for independent validation and detailed characterization. TkUGT80B1 triterpenoid glycosylating activity provided first evidence for triterpenoid saponin synthesis in T. koksaghyz latex. Based on its identified interaction partners, TkSRPP4 appears to play a special role in the endoplasmic reticulum, interacting with lipidmodifying enzymes that may facilitate rubber particle formation. TkSRPP5 appears to be involved in GTPase-dependent signaling and TkSRPP3 may act as part of a kinase signaling cascade, with roles in stress tolerance. TkSRPP interaction with TkUGT80B1 draws a new connection between TkSRPPs and triterpenoid saponin synthesis in T. koksaghyz latex. Our data contribute to the functional differentiation between TkSRPP paralogs and demonstrate unexpected interactions that will help to further elucidate the network of proteins linking TkSRPPs, stress responses and NR biosynthesis within the cellular complexity of latex.